2021
DOI: 10.3390/rs13071334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Detection of Mesoscale Outflow Boundaries Using Scatterometer Winds at Different Spatial Resolutions

Abstract: Outflow boundaries induced by cold-pools are a key characteristic of convective systems related to microphysical and kinematic processes during the mature stage of their lifecycle. Over the ocean, such kinematic processes are associated with low-level wind modulations that are captured by scatterometers. This study investigates the ability of the Advanced Scatterometer (ASCAT) wind retrievals to detect the outflow boundary associated with an oceanic mesoscale convective system (MCS). Leveraging a new technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…The small-scale wind variability in and near MCSs can be resolved by C-band fixed fanbeam space-borne scatterometers, such as the advanced scatterometer (ASCAT) on-board the MetOp series of satellites [6][7][8][9][10][11][12]. The potential of ASCAT to detect the horizontal wind divergence associated with individual MCS downdrafts was investigated by Kilpatrick and Xie [9], who concluded that ASCAT could reliably detect mesoscale (100-300 km) downdrafts, but not convective-scale (5-20 km) gust fronts.…”
Section: Down Outflow Down Outflowmentioning
confidence: 99%
“…The small-scale wind variability in and near MCSs can be resolved by C-band fixed fanbeam space-borne scatterometers, such as the advanced scatterometer (ASCAT) on-board the MetOp series of satellites [6][7][8][9][10][11][12]. The potential of ASCAT to detect the horizontal wind divergence associated with individual MCS downdrafts was investigated by Kilpatrick and Xie [9], who concluded that ASCAT could reliably detect mesoscale (100-300 km) downdrafts, but not convective-scale (5-20 km) gust fronts.…”
Section: Down Outflow Down Outflowmentioning
confidence: 99%
“…Several ocean-related variables have been identified for the ocean dynamic process, such as ocean currents, ocean tides, inner waves, ocean fronts, mesoscale vortices [1], etc. The oceanfront is an important branch of the ocean dynamic process [2][3][4]. Specifically, ocean fronts are located at the boundary between water masses with different properties [5,6], such as density, temperature, salinity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The method not only gets rid of the complex operations required for selecting the frames with ocean fronts from a video sequence but can also aggregate the information extracted from different classification methods. (2) We have created a new database for ocean-front trend recognition, to encourage other researchers to evaluate their methods for ocean-front trend classification and facilitate them in using data-driven methods, especially deep-learning-based methods, to deal with this challenging task.…”
Section: Introductionmentioning
confidence: 99%